Effect of Euxestophaga argentinensis (Hymenoptera, figitidae) on corn-silk fly larvae Euxesta sp. in two sweet corn planting dates - Bertolaccini, Isabel (2018)
Fil: Bertolaccini, Isabel. Universidad Nacional del Litoral. Facultad de Ciencias Agrarias. Departamento de Producción Vegetal; Argentina